2016
DOI: 10.1128/aac.01559-15
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Carbapenem-Nonsusceptible Enterobacterial Isolates Collected during a Prospective Interregional Survey in France and Susceptibility to the Novel Ceftazidime-Avibactam and Aztreonam-Avibactam Combinations

Abstract: An interregional surveillance program was conducted in the northwestern part of France to determine the prevalence of carbapenem-nonsusceptible Enterobacteriaceae (CNSE) isolates and their susceptibility to ceftazidime-avibactam and aztreonamavibactam combinations. Nonduplicate CNSE clinical isolates were prospectively collected from six hospitals between June 2012 and November 2013. MICs of ceftazidime and aztreonam, alone or combined with a fixed concentration of avibactam (4 g/ml), and those of carbapenems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
35
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 38 publications
6
35
1
Order By: Relevance
“…Also included are 13 isolates carrying MBLs and serine carbapenemases: VIM-1 and KPC-2 (n ϭ 4), IMP-4 and KPC-2 (n ϭ 2), VIM-4 and OXA-48 (n ϭ 2), VIM-31 and OXA-48 (n ϭ 1), NDM-1 and OXA-48 (n ϭ 3), and NDM-1 and OXA-232 (n ϭ 1). have been performed, and the frequency of noncarbapenemasemediated mechanisms among carbapenem-nonsusceptible Enterobacteriaceae has been found to be 77.2 to 98.6% (13,(32)(33)(34). These estimates exceeded the proportion observed here, but that is likely because those collections included ertapenem-nonsusceptible isolates, against which meropenem can retain some activity, whereas that was not the case in the present work (35).…”
contrasting
confidence: 56%
See 1 more Smart Citation
“…Also included are 13 isolates carrying MBLs and serine carbapenemases: VIM-1 and KPC-2 (n ϭ 4), IMP-4 and KPC-2 (n ϭ 2), VIM-4 and OXA-48 (n ϭ 2), VIM-31 and OXA-48 (n ϭ 1), NDM-1 and OXA-48 (n ϭ 3), and NDM-1 and OXA-232 (n ϭ 1). have been performed, and the frequency of noncarbapenemasemediated mechanisms among carbapenem-nonsusceptible Enterobacteriaceae has been found to be 77.2 to 98.6% (13,(32)(33)(34). These estimates exceeded the proportion observed here, but that is likely because those collections included ertapenem-nonsusceptible isolates, against which meropenem can retain some activity, whereas that was not the case in the present work (35).…”
contrasting
confidence: 56%
“…and ESBL-producing K. pneumoniae strains with impaired permeability (12). Ceftazidime-avibactam also displayed low MICs (Յ8 g/ml) against noncarbapenemaseproducing, carbapenem-nonsusceptible (NS) Enterobacteriaceae isolated from patients in France (13). Moreover, while recognizing that ceftazidime is not hydrolyzed significantly by OXA-48, but that bla OXA-48 -containing isolates of Enterobacteriaceae commonly also carry genes encoding ESBLs that do hydrolyze ceftazidime, ceftazidime-avibactam was found to be active against carbapenem-resistant, bla OXA-48 -positive Enterobacteriaceae (12,14).…”
mentioning
confidence: 99%
“…In contrast, we found MIC 50/90 of 0.5/ 1.5µg/ml for carbapenem non-susceptible strains. Another survey, which also characterized such isolates and their susceptibility to CA, reported MIC 50/90 , of 1/1µg/ml [20]. Although not assessed in our study, elevated MICs have been associated with KPC-3 strains of K. pneumoniae as well as strains with ESBLs and porin mutations and this is an area for future investigation [21].…”
Section: Discussionmentioning
confidence: 58%
“…For example, the incidence of resistance to the combination ceftazidime-avibactam (MIC Ն 16 g/ml) was 0.3% in a collection of 2,374 multidrug-resistant Klebsiella pneumoniae isolates that produced an Ambler class A enzyme and no class B, C, or D enzymes (17). Likewise, resistance to ceftazidime-avibactam was not detected in a collection of 139 non-carbapenemsusceptible Enterobacteriaceae (18). In agreement, the construction of large panels of isogenic strains of E. coli producing a single ␤-lactamase revealed that production of none of the TEM, CTX-M, KPC, CMY, ACT, FOX, PDC, GES, PER, VEB, and OXA enzymes that were tested, except PER-4, raised the MIC of ceftazidime above 8 g/ml when determined in the presence of avibactam (12,(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%